2015
DOI: 10.1021/jf5060672
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate Foliar Application to Tempranillo Vineyard Improved Grape and Wine Phenolic Content

Abstract: The importance of phenolic compounds for grape and wine quality has drawn attention to studying different practices with the aim of increasing their content. Cluster application of elicitors is a viticultural practice that has shown promising results in recent years. However, cluster application requires a previous defoliation, which is time-consuming and expensive. In the present study, methyl jasmonate was foliar applied to Tempranillo grapevines in order to study its effect on grape and wine phenolic compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
86
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 45 publications
21
86
7
Order By: Relevance
“…This treatment also induced the synthesis in the berries of 3‐ O ‐glucosides of petunidin and peonidin and trans ‐ p ‐coumaroyl derivatives of cyanidin and peonidin. The concentrations of trans ‐piceid, which is the most important stilbene in grapes, were improved in all of the samples through this methyl jasmonate foliar application . However, it has been shown that the responses for phenolic compounds to methyl jasmonate and benzothiadiazole applications to Monastrell, Merlot and Syrah grapevines depended on the variety .…”
Section: Biostimulants To Improve Grape and Wine Qualitymentioning
confidence: 96%
“…This treatment also induced the synthesis in the berries of 3‐ O ‐glucosides of petunidin and peonidin and trans ‐ p ‐coumaroyl derivatives of cyanidin and peonidin. The concentrations of trans ‐piceid, which is the most important stilbene in grapes, were improved in all of the samples through this methyl jasmonate foliar application . However, it has been shown that the responses for phenolic compounds to methyl jasmonate and benzothiadiazole applications to Monastrell, Merlot and Syrah grapevines depended on the variety .…”
Section: Biostimulants To Improve Grape and Wine Qualitymentioning
confidence: 96%
“…At the end of the ripening period, the BTH and MeJ‐treated grapes showed higher total anthocyanin concentrations than control grapes, the highest anthocyanin concentration being found in the MeJ‐treated grapes. Portu et al also found an increase in anthocyanin and stilbene contents in Tempranillo grapes and wines when the grapes were treated pre‐harvest with MeJ.…”
Section: Resultsmentioning
confidence: 89%
“…The MeJ‐treatment only increased the concentration of flavonols during the first few days of the ripening period, whereas during the last 3 weeks before harvest, the flavonol concentration of MeJ‐treated grapes did not differ from that of control grapes. Portu et al did not observe any effect of the application of three different elicitors on the flavonol concentration of grapes at the moment of harvest. Contrary to these results, in a 2‐year experiment in which MeJ and BTH were applied pre‐harvest to Monastrell grapes, Ruiz‐García et al showed that both treatments increased the flavonol content of grapes at harvest.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In this context, several techniques have been applied in postharvest grape storage, such as the use of refrigeration and modified atmosphere associated with the application of calcium chloride (DANNER et al, 2009;SILVA et al, 2012), also applied pre-harvest (RUIZ-GARCÍA et al, 2012;PORTU et al, 2015) as well as the association of pre-and postharvest treatments in other fruits, such as apples (SHARMA et al, 2013) and plums (MANGANARIS et al, 2008), aiming to promote an increase in fruit postharvest life, thus resulting in increased prospects of greater profitability.…”
Section: Introductionmentioning
confidence: 99%